Facial dimple creation surgery: A review of literature - M Kiran Kumar; Arka Kanti Dey; Dhirendra Kumar Singh; K N V Sudhakar; Rajat Mohanty (Wolters Kluwer Medknow Publications, 2017)
Cosmetic surgery is not a new thing. The boom of cosmetic surgery is at its pace in India; people have been getting habituated to esthetics for so many years. Esthetic adjustment of various body parts such as rhinoplasty and lip modifications are more common nowadays. A dimple is a small depression on the surface of the body which can be easily noticeable; people appreciate the presence of dimple on the face and believe that it is a sign of good fortune and prosperity. With the advancements in the cosmetic surgery, there has been a upsurge in having artificial dimple on face. With this increased demand in having facial dimples in people, surgeons now are in an idea of creating an artificial dimple with dimple surgery or "dimpleplasty." The procedure of dimpleplasty is as simple as making a cut in the skin, suturing the underside of the skin to a deeper layer to create a small depression. The suture creates a permanent scar which maintains the dimple. It is a thumb rule that any surgery has minor risks which are avoidable; the current review enumerates the various procedures for dimpleplasty and their outcomes. This article emphasizes on routine as well as recent procedures used for dimpleplasty and its relative complications.